Social participation, resilience, and coping tendency in a sample of stroke survivors: a multi-centre cross-sectional study in China - Xuan Zhou; Ying Wang; Lanshu Zhou (Medical Journals Sweden, 2024)
Objectives: To investigate the association between resilience and social participation and examine the mediation of resilience on coping strategies and social participation. Design: A multi-centre cross-sectional study performed from April to July 2022. Participants: The study sample comprised 239 stroke survivors (53.1% male). The mean age of participants was 65.4 years. Methods: The study was conducted at 3 neurorehabilitation centres in Shanghai, China. The Utrecht Scale for Evaluation of Rehabilitation Participation (USER-P) was used to measure both objective and subjective social participation. Resilience was evaluated using the Connor-Davidson Resilience Scale (CD-RISC), while positive coping tendency was assessed using the Simplified Coping Style Questionnaire (SCSQ). Multivariate linear regression was employed, taking into account confounding factors. In cases where a significant interaction effect was observed, simple slope analysis was conducted to explore the relationship between positive coping tendency and social participation at different levels of resilience. Results: The mean scores of social participation frequency, restriction, and satisfaction were 21.80 ± 15.13, 38.92 ±  26.48, and 63.34  ± 22.35, respectively. Higher resilience level was independently associated with higher social participation frequency (B = 0.210, p < 0.001), less participation restriction (B = 0.584, p < 0.001), and higher participation satisfaction (B = 0.250, p < 0.001). Moreover, higher resilience was correlated with more positive coping tendency. More positive coping tendency was related to higher social participation frequency and less participation restriction, but not to social participation satisfaction. Furthermore, individuals at different resilience levels moderated the effect of positive coping tendency on social participation frequency. Conclusion: This study underlines the importance of resilience as a potential intervention in enhancing both objective and subjective social participation in stroke survivors, and provides insights into increasing the efficacy of positive coping strategies on social participation.